Terrorism and the Media: Patterns of Occurrence and Presentation, 1969-1980 - Delli Carpini, Michael X (1984)
What we have to do is tell people about what's going on in the world. This quote from Ted Koppel, an ABC anchorman, taken from a recent TV commercial for the network news, captures the key focus of this paper. To what extent does television news accurately inform its viewers about what is going on in the world? We begin to answer this question by focusing on one topic which is both of political significance and has received a large amount of coverage from the networks: International terrorism. (I) By comparing the amount and type of coverage which international terrorism received from the networks over the period 1969 to 1980 to a more systematic set of data based upon world-wide reports of international terrorism over the same period, we can test the degree to which viewers are provided with an accurate picture of what international terrorism is, where it is happening, against whom, and how often. In addition, we look more closely at network treatment of a single terrorist incident to speak to the more subtle ideological aspects of media coverage. The organization of this paper is as follows. In the next two sections we examine television news in general terms, discussing its strengths and weaknesses as a provider of information, considering previous theoretical and empirical work on the topic, and laying out our expectations. In the fourth section we give the details of our specific analysis, discussing the choice of international terrorism, operationalizing concepts, describing the data sets, and explaining the methods. Section five is a presentation of results with a brief discussion. Section six is a more detailed case study of coverage of the seizure of the Dominican Republic Embassy in Colombia in 1980. The final section consists of a summary, discussion and some concluding remarks concerning network coverage of international terrorism, and the larger questions of television as a source of political information and political agendas